Oncomodulin: The Enigmatic Parvalbumin Protein - Climer, Leslie K.; Cox, Andrew M.; Reynolds, Timothy J.; Simmons, Dwayne D. (Frontiers in Molecular Neuroscience, 2019)
EF-hand Ca2+-binding protein family members, - and -parvalbumins have been studied for decades. Yet, considerable information is lacking distinguishing functional differences between mammalian -parvalbumin (PVALB) and oncomodulin (OCM), a branded -parvalbumin. Herein, we provide an overview detailing the current body of work centered around OCM as a Ca2+-binding protein and describe potential mechanisms of OCM function within the inner ear and immune cells. Additionally, we posit that OCM is evolutionarily distinct from PVALB and most other -parvalbumins. This review summarizes recent studies pertaining to the function of OCM and emphasizes OCM as a parvalbumin possessing a unique cell and tissue distribution, Ca2+ buffering capacity and phylogenetic origin.